Dynamic thiol-disulfide balance in patients with chronic sinusitis with and without nasal polyposis - Sevil, Ergun; Gul, Fatih; Oguzhan, Tolga; Bercin, Sami; Neselioglu, Salim; Bicer, Cemile (Annals of Medical Research, 2021)
Aim: Reactive oxygen species (ROS) have a crucial role in the pathogenesis of chronic rhinosinusitis (CRS). The current study investigates a novel oxidative stress marker (thiol (SH)/disulfide (SS) homeostasis) in patients with CRS with and without nasal polyposis (NPs).Materials and Methods: A total of 167 subjects, including 94 patients with CRS and 73 healthy controls, were included in the study. The patients were subdivided into two groups those with CRS with NP and those with CRS without NP. Comparisons were made between the groups in respect of serum native SH, total thiol (TT), and SS levels and the SS/SH and SS/TT ratios. Results: There was no significant difference in TT between the CRS with the NP group and the CRS without the NP group (p> 0.05). There was a significant difference (p 0.05) between the CRS without the NP group and the control group in %SH/TT, %SS/TT, %SS/SH, SS, and SH. A significant difference (p 0.05) was found between the CRS with the NP group and the control group in %SH/TT, %SS/TT, %SS/SH, SS and SH values. Conclusion: Dynamic SH/SS homeostasis shifts towards SS formation as a result of SH oxidation in patients with CRS.
Keywords: Chronic sinusitis; nasal polyp; oxidative stress; sulfhydryl compounds